EXPERIMENTAL ANALYSIS OF CASTOR OIL AND DIESEL OIL MIXTURES IN A 4-STROKE COMPRESSION COMBUSTION ENGINES: EXPERIMENTAL ANALYSIS OF CASTOR OIL AND DIESEL OIL MIXTURES IN A 4-STROKE COMPRESSION COMBUSTION ENGINES - Suardi, Suardi; Alamsyah, Alamsyah; Nugraha, Andi Mursid; Pawara, Muhammad Uswah (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
The production of hydrocarbon fuels shows a downward trend which forces people to look for alternative renewable fuels such as biodiesel from vegetable oil. One solution that can be applied in the use of biodiesel mixed with castor oil. The purpose of this study was to determine the effect of using a mixture of castor oil on the performance of diesel engines. The method used in this experiment is testing it directly on a diesel engine. Experiments were carried out on machines with a load of up to 4000 watts by mixing pure diesel fuel with castor oil to produce biodiesel B10, B20, and B30 as fuel. The results showed that the use of castor oil biodiesel tends to be lower than diesel oil, the torque produced by B20 17,59 N.m is greater than diesel oil, and the thermal efficiency of B20 17,04 % and SFC B20 is 470,2 gr/kWh more economical than diesel oil. B20 provides better performance values foe diesel engines and this is the right solution to be an alternative fuel other than diesel oil.